A history of the animal world in the ancient Near East - Collins, Billie Jean. (Leiden ; Boston : Brill, 2002)
This title concerns man's contact with the animal world: sacrifice, sacred animals, diet, and domestication. Chapters on art, literature, religion and animal husbandry reveal a picture of the complex relationships between the peoples of the Ancient Near East and (their) animals.
List of Figures; List of Tables; Part I: The Native Fauna; Part II: Animals in Art; Part III: Animals in Literature; Part IV: Animals in Religion; Part V: Studies in the Cultural Use of Animals; Appendix: Bibliography of Near Eastern Zoology; References; Index.
Includes bibliographical references (pages 537-601) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Human-animal relationships -- Middle East; Animals in art; Animals in literature; Animals -- Religious aspects; Animals in the Bible; Relations homme-animal -- Moyen-Orient.; Animaux dans l'art.; Animaux dans la littérature.; Animaux -- Aspect religieux; Animaux dans la Bible; SOCIAL SCIENCE -- Human Geography; Animals in art; Animals in literature; Animals in the Bible; Animals -- Religious aspects; Human-animal relationships; Middle East; Altertum; Tierdarstellung; Tiere; Alter Orient; Naher Osten; Relation homme-animal.; Thème artistique; Animal; Thème littéraire.; Aspect religieux; Antiquité; Moyen-Orient.; Samfundsvidenskab -- Sociologi